141 Guillain-Barre as a post-operative syndrome following resection of anaplastic astrocytoma. Issue 6 (27th May 2022) - Leahy, Christopher; Lavin, Tim; Gosal, David; Herwadkar, Amit; D'Urso, Pietro; Cahill, Varduhi
Abstract : We present a case of Guillain Barre Syndrome (GBS) following resection of a brain neoplasm. A 43 y.o. man presented with diplopia and lower back pain 2 weeks after resection of left mesiotemporal and fusiform gyrus grade III IDH 1 mutant anaplastic astrocytoma. Within a week he was unable to ambulate due to marked leg weakness. Examination showed bilateral weakness of lateral rectus muscles and lower motor bilateral facial weakness. Hip flexion was 1/5 bilaterally, otherwise 0/5. Tone was flaccid. Lower limb reflexes were absent and plantar responses were mute. Imaging showed no evidence of tumour recurrence or drop metastasis. CSF analysis demonstrated raised WCC (43/ul WBCs, <1/ul RBCs), protein was markedly elevated at 4.33 g/l and glucose normal. Cytology was negative for malignancy consist- ently. He was treated 5-days of intravenous immunoglobulin (2g/kg). He walked without assistance on discharge and his recovery was sustained at 6 months follow up. Neurophysiology showed a generalised, non- length dependent, motor> sensory, demyelinating neuropathy. This case highlights the importance of considering GBS as a potential cause of progressive neurological deficit in the postoperative period where "atypical" CSF findings are confounded by the preceding neurosurgical intervention. christopherleahy@doctors.org.uk